2018
DOI: 10.1016/j.athoracsur.2017.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes After Neoadjuvant Chemotherapy and Ipilimumab for Non-Small Cell Lung Cancer

Abstract: This report is the first to demonstrate the safety and feasibility of surgical resection after treatment with ipilimumab and chemotherapy in stage II-IIIA non-small-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
104
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 15 publications
8
104
3
Order By: Relevance
“…Most of the available studies were performed in advanced/metastatic recurrent NSCLC. Two studies were done in the neoadjuvant setting (25)(26)(27)(28). In a phase I study (25,26), 21 eligible patients with stage IB-IIIA resectable NSCLC received two doses of nivolumab (3 mg/kg) on days 28 and 14 before surgical resection.…”
Section: Phase I-ii Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the available studies were performed in advanced/metastatic recurrent NSCLC. Two studies were done in the neoadjuvant setting (25)(26)(27)(28). In a phase I study (25,26), 21 eligible patients with stage IB-IIIA resectable NSCLC received two doses of nivolumab (3 mg/kg) on days 28 and 14 before surgical resection.…”
Section: Phase I-ii Studiesmentioning
confidence: 99%
“…No unexpected adverse event and no operative mortality were observed (26). The primary objective of the phase II study (27,28) was "to assess whether the appearance of T cells activated against select tumor-associated antigens (TAA) increased from baseline following treatment with ipilimumab" and this endpoint was not met. Twenty-four stage IIA-IIIA NSCLC received 3 cycles of induction cisplatin or carboplatin plus paclitaxel with ipilimumab (10 mg/kg) during cycles 2 and 3.…”
Section: Phase I-ii Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…26 These low mortality rates may continue with neoadjuvant immunotherapy. Yang and colleagues 27 reported a 0% mortality for 13 patients (10/13 IIIA) given neoadjuvant ipilimumab with a platinum doublet in the TOP1201 trial and no difference in morbidity rates from those previously reported in other preoperative chemotherapy trials. Despite these encouraging results, future studies will need to define morbidity and mortality as it relates to the addition of immunotherapies and toxicities that were well described previously.…”
Section: Safety Of Stage Iiia Surgerymentioning
confidence: 87%
“…Regardless, the association between cell proliferation and immune suppression in stage I cancers holds relevance, as stage IB tumors are often included in trials of neoadjuvant and adjuvant T-cell checkpoint inhibition in NSCLC. 7,8 Therefore, if Ki67 expression does predict response to therapy, this might help to select patients for this treatment approach. The authors' finding that high Ki67 expression (>25% of tumor cells) was associated with increased mortality may provide an additional rationale for the use of multimodality treatment in this patient population.…”
Section: Matthew J Bott MDmentioning
confidence: 99%